DEVELOPMENT OF LEARNING MEDIA ON PROCEDURAL TEXT MATERIAL USING IMAGES TO IMPROVE SPEAKING SKILL AT SMA NEGERI 2 RIMBA MELINTANG GRADE XI - Lestari, Rizki; Panjaitan, Erlia Utami; Atnur, Witma Novita; Ritonga, Syahraini; Alfanisa, Desi (Nusantara Hasana Journal, 2025)
This research aims to improve speaking skills, by using procedural texts and overcoming lack of confidence, as well as the limited vocabulary they know in class XI. Speaking is a productive skill that produces words and sentences orally. Supplementary speaking make a picture that is helpful in teaching English was developed to help them become more proficient speakers. as the conviction that study is the foundation of learning. Thirty students from SMA Negeri 2 Rimba Melintang's class XI-2 served as the study's sample. The supplementary speaking product is appropriate for application and implementation, as evidenced by the average data from the haunted questionnaire, which was collected by questionnaire completion. The growth of supplemental speaking has good appeal and credentials, as demonstrated by the test results of students in class XI-2 at SMA Negeri 2 Rimba Melintang. The validity percentage is 80%, indicating that supplemental speaking is appropriate for use as a teaching tool